​if f(1)=3 and f(n)=-2f(n-1) 1, then f(5)=

Algebra
Tutor: None Selected Time limit: 1 Day

if f(1)=3 and f(n)=-2f(n-1)+1, then f(5)=

May 8th, 2015

if f(1)=3 and f(n)=-2f(n-1) 1, then f(5)=


Arithmetic sequences can be converted into functions of the form A(n) = A(1) + (n – 1)d where A(n) is the value of the nth term, A(1) is the value of the first term, n is the term number, and d is the common difference between the terms. 

f(5)=3-2f
May 8th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
May 8th, 2015
...
May 8th, 2015
Dec 5th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer